The Impact of Generative AI on Modern Software Development: Revolutionizing the Development Lifecycle - Tejeswar Reddy Velpucharla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Generative Artificial Intelligence (GenAI) on software development practices. The article examines how GenAI is revolutionizing various aspects of the development lifecycle, from code generation and testing to team collaboration and ethical considerations. The article analyzes the emergence of AI-powered development tools, their impact on workflow automation, and the democratization of software development. It also addresses the challenges and implications for workforce evolution, emphasizing the importance of ethical considerations in AI implementation. Through this article current trends and future projections, the article provides insights into how organizations can effectively integrate GenAI while maintaining high standards of quality and ethical responsibility in software development.